The halal standard: From the regulatory norms of eating behavior to large sectors of the economy - Valiev A.R.; Yazid Yaacob; Nezhmetdinova F.T.; Kalimullin M.N.; Salikhov R.T.; Parfenova K.A. (BIO Web of Conferences)
This article examines the evolution of the term “halal” using the example of Russia and Malaysia, from a religious dietary prescription to achieving the modern status of a significant economic force. The article analyzes how halal has transformed into a commercial product, as well as the impact of the regulatory framework, certification processes and technological innovations on its integration into the large-scale economy. The study focuses on the need for joint research work by Russian and Malaysian scientists aimed at using their unique experience to solve key tasks of harmonizing global halal standards, stimulating innovation in the field of halal food technologies and increasing consumer confidence, as well as market access.